(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Medico-legal cases (MLCs) form a critical part of emergency medicine practice, requiring meticulous documentation, legal compliance, and seamless coordination between healthcare providers and law enforcement agencies. Handling medico legal cases in the Emergency Medicine department of a busy tertiary care hospital is associated with lot of chal lenges that can affect the quality of patient care and the integrity and quality of legal processes. This article examines the key aspects of effective and professional MLC management, highlighting best practices for accurate documentation, ethi cal considerations, and timely legal reporting. Common challenges, such as inadequate staff training, lack of standardized protocols, and communication gaps, are discussed. Practical solutions, including staff training, digital documentation, and streamlined communication strategies, are proposed to enhance medico-legal case handling. By implementing these strategies, emergency departments can optimize medico-legal case handling, ensuring legal integrity, patient rights pro tection, and improved emergency care services. This article serves as a guide for healthcare professionals to handle MLC complexities with confidence and professionalism